Noise-Induced Hearing Loss related to Personal Music Players- Awareness Level among the Young users in a Developing Country - sadaf zia; Mehboob Afzal Jawaid; Mohammad Bilal; Tooba Farooqui; Fatemah Lakhani; Lubna Tabassum; Salman Matiullah Shaikh (Journal of the Dow University of Health Sciences, 2014)
Introduction: